Restoration Comedy - Burns, Edward. author. aut Link
VIII, 283 p.
Keywords: What is Restoration comedy? What pleasure does it offer its audience, and what significance does it find in exploring that pleasure? Edward Burns here provides a new account of the origins and nature of Restoration comedy as a distinct genre. The book enlarges the usual focus with a wider range of writers than the conventional ossified canon taking in a revaluation of many rarely studied dramatists, a reconsideration of pastoral, and the instatement of women writers as major contributors to the culture of the age. It offers a substantial and original interpretation of one of the most intriguing of seventeenth-century literature forms.